PAG--a multipurpose transmembrane adaptor protein - Hrdinka, M; Horejsi, V (Oncogene, 2014)
Phosphoprotein associated with glycosphingolipid-enriched microdomains (PAG), also known as Csk-binding protein (Cbp), is a ubiquitously expressed transmembrane adaptor protein present in lipid rafts and involved in a number of signaling pathways. It helps recruit cytoplasmic C-terminal Src kinase (Csk) to lipid raft-associated Src kinases, mediates a link to actin cytoskeleton and interacts with several other important cytoplasmic and plasma membrane-associated proteins. In recent years, PAG has been implicated in various aspects of cancer cell biology. Our review covers all so far published data on this interesting protein.
Keywords: signální transdukce; Neoplasms; Gene Expression Regulation, Neoplastic; lidé; membránové mikrodomény; Signal Transduction; Humans; Animals; mikrofilamenta; CSK Tyrosine-Protein Kinase; src-Family Kinases; fosforylace; Actin Cytoskeleton; zvířata; nádory; skupina kinas odvozených od src-genu; C-terminální Src kinasa; Membrane Proteins; membránové proteiny; regulace genové exprese u nádorů; Phosphorylation; Membrane Microdomains